2019
DOI: 10.1186/s13098-019-0434-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal genetic contribution to pre-pregnancy obesity, gestational weight gain, and gestational diabetes mellitus

Abstract: Introduction Pre-pregnancy obesity, gestational diabetes mellitus (GDM), and gestational weight gain (GWG) are associated with each other. This is the first study to investigate whether genetic variants were associated with having GDM, and whether genetic variants-related GDM were associated with adiposity including pre-pregnancy obesity and excessive GWG in Turkish women. Patients and methods Women with GDM (n = 160) and without GDM (n = 145) were included in case-cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
2
9
0
1
Order By: Relevance
“…The results of sensitivity analysis are shown as forest maps in Supplementary 2. For rs1544410, the results fluctuated greatly after omitting El-Beshbishy 2015 [25] and for rs731236, the results fluctuated greatly after omitting Rahmannezhad 2016 [26] or Zhu 2019 [27].…”
Section: Subgroup Analysis and Sensitivity Analysismentioning
confidence: 99%
“…The results of sensitivity analysis are shown as forest maps in Supplementary 2. For rs1544410, the results fluctuated greatly after omitting El-Beshbishy 2015 [25] and for rs731236, the results fluctuated greatly after omitting Rahmannezhad 2016 [26] or Zhu 2019 [27].…”
Section: Subgroup Analysis and Sensitivity Analysismentioning
confidence: 99%
“…( 68 ) have reported that p.Ala98Val is not associated with the age during the diabetes diagnosis of HNF1A -MODY individuals. Previous studies have reported that there is no relationship between this variant and gestational diabetes in Danish ( 69 ), Polish ( 70 ), and Turkish ( 71 ) women. The role of HNF1A p.Ala98Val variant in early and late-onset of diabetes and MODY 3 differs between populations ( 67 , 72 , 73 ).…”
Section: Resultsmentioning
confidence: 84%
“…The main characteristics of all the studies included in our study were shown in Table 1 . There were 5 case–control studies on BsmI (rs1544410) [ 14 17 , 19 ], 4 case–control studies on TaqI (rs731236) [ 13 16 ], 3 case–control studies on FokI (rs2228570) [ 14 , 15 , 17 ] and 3 case–control studies on ApaI (rs7975232) [ 13 15 ]. 15 independent studies consisted of 4 Asian [ 16 , 19 ], 3 African [ 17 ] and 8 Caucasian populations [ 13 15 , 18 ].…”
Section: Resultsmentioning
confidence: 99%